(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The question of the possibilities of combining words, phrases and other units of one language with units of another language, as well as the characteristics of the resulting combinations, has always been of interest in the field of linguistics, both in world linguistics and in Uzbek linguistics, in all periods. This interest stems from the fact that language units can express different meanings depending on their context. Moreover, the instrumental means chosen as objects of research reveal their grammatical functions in combinations that can be changed. In this respect, the analysis of word combinations, phrases and collocations linking verbs with verbs plays an important role in ensuring correct translation from one language to another.